A Framework For Thinking About Enterprise Formalization Policies In Developing Countries - Kenyon, Thomas (The World Bank, 2007)
What policies encourage firms to become formal? The standard approach emphasizes reducing the costs of compliance with government regulation. This is unlikely to be sufficient. Instead we need to understand compliance as a function not only of firm-level costs and benefits but also in terms of the interaction between the firm and its competitors and between the firm and the state. This paper emphasizes the coordination and credibility issues involved in promoting formalization and discusses possible institutional solutions, among them business associations that make the benefits of membership dependent on compliance, information sharing arrangements among government agencies and improvements in the quality of public management